2021
DOI: 10.1002/jlb.1a0820-501r
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG12 alleviates hypertensive vascular endothelial injury through miR-25-3p/SIRT6 pathway

Abstract: The objective of this study was to find the role of LncRNA SNHG12 in the regulation of hypertensive vascular endothelial injury. LncRNA SNHG12 and miR‐25‐3p expression were detected by quantitative RT‐PCR. Protein levels of Sirtuin 6 (SIRT6), endothelial cell (EC) senescence markers p16 and p21, and EC marker CD31 were measured by Western blot. The apoptosis of HUVECs was detected by flow cytometry. The binding between LncRNA SNHG12 and miR‐25‐3p was verified by dual luciferase reporter gene assay and RNA pull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…The protective role of Snhg12 in the vessel wall was also revealed by a separate study ( Qian et al, 2021 ). Snhg12 expression was also reduced by Ang II in HUVECs.…”
Section: Long Noncoding Rnas In Cellular Senescence Of Vascular Endotheliummentioning
confidence: 60%
See 1 more Smart Citation
“…The protective role of Snhg12 in the vessel wall was also revealed by a separate study ( Qian et al, 2021 ). Snhg12 expression was also reduced by Ang II in HUVECs.…”
Section: Long Noncoding Rnas In Cellular Senescence Of Vascular Endotheliummentioning
confidence: 60%
“…Snhg12 expression was also reduced by Ang II in HUVECs. The overexpression of Snhg12 inhibited EC senescence in vitro through a miR−25−3p/SIRT6 pathway and alleviated vascular endothelial injury in Ang II−induced hypertensive mice ( Qian et al, 2021 ).…”
Section: Long Noncoding Rnas In Cellular Senescence Of Vascular Endotheliummentioning
confidence: 99%
“…Some studies suggested that SIRT6 is regulated by miRNAs and lncRNAs ( e.g. , miR-25-3p, LncRNA Blnc1, and LncRNA SNHG12) in vascular cells in vitro [ 107 , 108 ]; however, the mechanisms by which SIRT6 is repressed in aging and aging-related vascular diseases remain unclear. Further studies of the detailed mechanism underlying the aging-mediated decline in SIRT6 expression and activity will improve the understanding of SIRT6 and promote the design of SIRT6-targeted therapeutic translational strategies.…”
Section: Conclusion Remarks and Perspectivesmentioning
confidence: 99%
“…In angiotensin II (Ang II)-induced hypertensive mice and Ang II-induced HUVEC injury models, Qian et al [ 36 ] found that the expression of lncRNA SNHG12 was significantly downregulated. The overexpression of lncRNA SNHG12 targeted miR-25-3p to increase the expression of sirtuin (SIRT) 6.…”
Section: Role Of Lncrnas At the Cellular Levelmentioning
confidence: 99%